EVALUATING THE INFLUENCE OF PHYSICIAN EXPERTISE AND PROCEDURAL VOLUME ON COMPLICATION RATES AND PATIENT SATISFACTION IN EMERGENCY MEDICINE AND PLASTIC SURGERY - Faisal Ayidh M. Alanazi, Faisal Ali Alshammari, (Chelonian Research Foundation, 2022)
This study investigates the impact of physician expertise and procedural volume on complication rates and patient satisfaction in emergency medicine and plastic surgery. A retrospective analysis of patient records and surveys was conducted at two major hospitals in Saudi Arabia over a five-year period. The study included 500 emergency medicine patients and 500 plastic surgery patients, along with their attending physicians. Physician expertise was determined by years of experience and specialty certification, while procedural volume was measured by the number of procedures performed annually. Complication rates were assessed using ICD-10 codes, and patient satisfaction was evaluated through a validated survey. Logistic regression analysis was used to examine the associations between physician factors and patient outcomes, while controlling for patient demographics and clinical characteristics. The results showed that higher physician expertise and procedural volume were significantly associated with lower complication rates and higher patient satisfaction in both specialties. The findings suggest that investing in physician training and specialization, as well as ensuring adequate exposure to procedures, can improve the quality and safety of patient care in emergency medicine and plastic surgery. The study highlights the importance of continuous professional development and performance monitoring in these critical areas of healthcare.